2015
DOI: 10.1371/journal.pone.0135989
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c Test as a Tool in the Diagnosis of Gestational Diabetes Mellitus

Abstract: AimsGestational diabetes mellitus (GDM) is a prevalent and potentially serious condition which may put both mothers and neonates at risk. The current recommendation for diagnosis is the oral glucose tolerance test (OGTT). This study aimed to determine the usefulness of HbA1c test as a diagnostic tool for GDM as compared to the traditional criteria based on the OGTT.MethodsThis was a diagnostic test accuracy study. We performed OGTT and HbA1c test in women attending prenatal visits at a tertiary hospital. GDM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 27 publications
5
67
1
2
Order By: Relevance
“…In our study using WHO 75 g OGTT criteria, the prevalence of GDM as per WHO OGTT criteria was 19.6% (51/260). In another study by Renz et al . the prevalence of GDM was reported to be 33%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our study using WHO 75 g OGTT criteria, the prevalence of GDM as per WHO OGTT criteria was 19.6% (51/260). In another study by Renz et al . the prevalence of GDM was reported to be 33%.…”
Section: Discussionmentioning
confidence: 90%
“…In our study using WHO 75 g OGTT criteria, the prevalence of GDM as per WHO OGTT criteria was 19.6% (51/260). In another study by Renz et al 17 the prevalence of GDM was reported to be 33%. Conversely, Soumya et al 18 and Khalafallah et al 11 reported a lower prevalence of GDM at 9% and 11.9%, respectively, using the OGTT criteria.…”
Section: Discussionmentioning
confidence: 90%
“…[19] Another study from Brazil which evaluated the performance of HbA1c as diagnostic tool for GDM showed that a cutoff of 5.4% (36 mmol/mol) has the optimal sensitivity and specificity, but the sensitivity of 70% is still not satisfactory. [20]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that pregnancy-specific HbA1c reference ranges could be developed to reduce those patients requiring OGTT 67. In a 2015 study, a threshold of 5.8% had a sensitivity of 26.4% and specificity of 94.9% with 38% of participants diagnosable based on HbA1c alone 68. Furthermore, use of HbA1c in this manner may facilitate screening a wider population, thereby detecting patients with GDM who fail to complete or are not detected by an OGTT 69.…”
Section: Erythrocyte Turnovermentioning
confidence: 99%